Interacción entre los diversos actores educativos para el fortalecimiento de sus capacidades en una institución educativa - Morales Rojas, Jenny Estela (2024)
The present article is the result of research conducted to analyze the influence of interaction and communication among educational actors in strengthening their capacities at Nuestra Sra. de las Mercedes School in Ica in the year 2011. The study employed a quantitative methodology, a pre-experimental design, utilizing the observation technique. The evaluative observation scales were applied to 27 female class presidents, 35 teachers, 32 parents, and 18 administrative staff. Data were statistically processed using the average differences, standard deviation of differences, and the student's paired T-test. In the statistical results, analyzing the data from the tests applied to class presidents, teachers, parents, and administrative staff, Tc > Ttabular, and P < 0.01. In conclusion, the research hypothesis has been demonstrated: interaction and communication among various educational actors significantly strengthen their capacities at Nuestra Sra. de las Mercedes School.